Impact of Endocrine-Disrupting Chemicals, Climate, and Air Pollution on Pregnancy Outcomes: A Scoping Review - Wesley, Shaun R.; Gallo, Mary; Apata, Tejumola; Dis, Jane van; Hollenbach, Stefanie J. (Seminars in Reproductive Medicine, 2024)
Environmental pollutants, including endocrine-disrupting chemicals (EDCs), air pollution, and climate change, are increasingly recognized for their potential impact on pregnancy outcomes. EDCs, found in pesticides, industrial chemicals, and personal care products, are associated with preterm birth and fetal growth restriction, primarily through hormonal interference. Air pollution, notably PM2.5, NO2, and O3, has been linked to increased rates of preterm birth, low birth weight, and stillbirth. Climate factors, such as extreme heat, elevate risks of pregnancy loss and preterm birth, with significant impacts on vulnerable populations across diverse socioeconomic and geographic regions. These exposures contribute to adverse pregnancy outcomes through mechanisms involving oxidative stress, inflammation, and endocrine disruption. The interplay among these environmental factors underscores the need for integrated, longitudinal studies to understand their combined effects on pregnancy outcomes better. Future research should focus on region-specific impacts, cumulative exposure, and policy-driven interventions to mitigate these environmental risks, especially in vulnerable populations disproportionately affected by these hazards. This scoping review synthesizes recent findings from 2019 to 2024 to highlight these associations and identify research gaps.
Keywords: adverse pregnancy outcomes; endocrine-disrupting chemicals; air pollution; climate change